Contemporary art in the Federal Republic of Germany : 12 collections of 30 graphics : Art centres Düsseldorf. - Herzogenrath, Wulf (Stuttgart : IFA - Institut für Auslandsbeziehungen Stuttgart, 1978)
Becher, Bernd & Hilla ; Beuys, Joseph ; Böhmler, Claus ; Geiger, Rupprecht ; Heerich, Erwin ; Klapheck, Konrad ; Mack, Heinz ; Piene, Otto ; Richter, Gerhard ; Roth, Dieter ; Sauer, Michel ; Uecker, Günther ; Wewerka, Stefan ; Wiegand, Gottfried ; Wilding, Ludwig
Biog. [1 p.]
12 collections of 30 graphics. Each will provide a survey of contemporary graphic art in the Federal Republic of Germany in a sequence of exhibitions appearing at regular intervals. They are entitled "Tournee-Ring". (...) Planned and selected in 1974 by Dr. Götz Adriani, (...) Dr. Wulf Herzogenrath (...) Organized by the Institute for Foreign Cultural Relations
Engels
boek
Keywords: Duitsland; Düsseldorf